Interaction between density and Cu toxicity for Enchytraeus crypticus and Eisenia fetida reflecting field scenarios - Menezes-Oliveira, VB
Effect assessment is usually based on responses obtained from standard tests, in which organisms are well fed and in an optimal population density. For a more thorough assessment of ecotoxicological risk, information is needed for chemical effects in systems that closer reflect the potential exposure in the field systems. Responses measured in standard density experiments do not fully reflect the field scenario, where populations' size fluctuate with environmental conditions, leading to very low organism number in certain season/conditions and high number in others. In the present study, the possible interaction between density and Cu-pollution was investigated in regard to population growth, using Enchytraeus crypticus, and for individual juvenile growth, using Eisenia fetida. The standardized ISO and OECD guidelines for enchytraeids and earthworms were adapted to test four densities and four Cu concentrations. The final population number was used to assess the effects and possible interaction between densities and Cu toxicity for population responses and the increase in individual organism wet weight was used as growth response. The study showed that although initial density itself had tremendous impact on population and individual growth, organisms under different densities had the same sensitivity to Cu. (C) 2011 Elsevier B.V. All rights reserved.